Maggot Moon - Gardner, Sally (UK, 2012)
What if the football hadn't gone over the wall? What if Hector had never gone looking for it? What if he hadn't kept the dark secret to himself? What if...? The I suppose I would be telling myself another story. You see, the what ifs are as boundless as the stars...
Keywords: Historical; Juvenile Fiction; Science Fiction